Transcriptome Profile in Hippocampus During Acute Inflammatory Response to Surgery: Toward Early Stage of PND - Xiang, Xuwu; Yu, Yang; Tang, Xiaodong; Chen, Manli; Zheng, Yueying; Zhu, Shengmei (Frontiers in Immunology, 2019)
Perioperative neurocognitive disorders (PND) are common complications among surgical patients which result in long-term morbidity and mortality. Role of neuroinflammation are strongly implicated underlying the pathophysiology of PND, but there are still no effective treatments. In this study, transcriptome analysis was designed to investigate the underlying molecular mechanisms during acute inflammatory response to surgery. By using ELISA, a significant elevated IL-6 was observed both in circulating system and central nervous system and peaked at 6 hours post-surgery, but transiently returned to baseline thereafter. Hippocampus were collected at 6 hours post-surgery then processed for RNA-Seq. A total of 268 genes were screened differentially expressed between the Surgery and Control group, including 170 up-regulated genes and 98 down-regulated genes. By functional enrichment analysis of differently expressed genes, several KEGG pathways involved in inflammatory mediator regulation of TRP channels, neuroactive ligand-receptor interaction and cholinergic synapse were overrepresented. Moreover, 15 dysregulated genes of interest were validated by quantitative real-time PCR and exhibited similar changes to the gene expression analyses. These results suggest that brain functions are greatly disturbed acutely after surgery and provide a comprehensive insight into global gene expression changes on acute presence of hippocampal inflammation and early stage of PND.